Building Wealth Buying Foreclosures - Schaub, John (Maidenhead McGraw-Hill Professional, 2008)
Foreclosures are one of the biggest real estate investment opportunities available in today's market. This title helps you target top properties and get the best deal, with tips on how to avoid scams, insight into the lender's perspective, and a checklist that helps you keep track of every step of the way.
Include Index and Illustrations
Keywords: Real estate investment